Efficacy of Fetal Wharton’s Jelly Mesenchymal Stem Cells-Derived Small Extracellular Vesicles in Metabolic Syndrome - Illayaraja Krishnan; Magdalene Tan Mei Ling; Min Hwei Ng; Jia Xian Law; Mohd Rafizul Mohd Yusof; Thavachelvi Thangarajah; Zalina Mahmood; Nurul Izzati Uda Zahli; Shathiya Rajamanickam; Baskar Subramani; Yogeswaran Lokanathan (Biomolecules)
Background/Objective: Metabolic syndrome (MetS) is characterized by abdominal obesity, increased blood pressure (BP), fasting blood glucose (FBG) and triglyceride levels, and reduced high-density lipoprotein (HDL) levels. This study aims to investigate the efficacy of the Wharton’s jelly mesenchymal stem cells (WJMSCs)-derived small extracellular vesicles’ (sEVs) preparations in managing MetS. Method: Twenty-four rats were fed with a high-fat and high-fructose diet to induce MetS for 16 weeks and randomized into three groups (n = 8/group): a MetS Control group treated with normal saline, MetS Low Dose (LD) group treated with a LD of sEVs preparations (3 × 109 particle/rat), and MetS High Dose (HD) group treated with a HD of sEVs preparations (9 × 109 particles/rat). The Control Non-Disease (ND) group was given a standard rat diet and autoclaved tap water with normal saline as treatment. Treatments were given via intravenous injection every three weeks for twelve weeks. Rats were assessed every six weeks for physical measurements, FBG, lipid profiles, CRP, leptin, adiponectin, and BP. Necropsy evaluation was performed on the lungs, liver, spleen, and kidney. Results: Significant reductions in FBG, triglycerides, BP, and increased HDL levels were observed in the treated groups compared to the control group. However, significant abdominal circumference (AC) improvement was not observed in the treated groups. Non-significant associations were found between fasting CRP, leptin, and adiponectin levels with MetS rats after treatment. In addition, sEVs preparations improved inflammation and hemorrhage in the lung and mineralisation in the renal of the treated group. Conclusions: Human fetal WJMSCs-derived sEVs preparations improve all the clusters of MetS in rats except AC and could be further explored as a treatment for MetS.